Pertanggung Jawaban PT. Indonesia Weda Bay Industrial Park Atas Kerusakan Lingkungan Hidup - Ghali Nugroho Adji; La Ode Angga; Marselo Valentino Geovani Pariela (PATTIMURA Law Study Review, 2023)
ABSTRACT: The function of the environment which has been supporting the daily needs of the community has been converted into a nickel (Ni) processing industrial area by the Indonesian Limited Liability Company Weda Bay Industrial Park (PT. IWIP). Purposes of the research to explain the form of legal liability to know and analyze the requirements so that the case of the Indonesian Limited Liability Company Weda Bay Industrial Park (PT. IWIP) for environmental damage caused by the processing of nickel mines can be subject to the principle of strict liability. This study uses a type of normative legal research. The processing techniques for legal materials that have been collected are carried out through stages; inventory, identification, classification, and systematization. Meanwhile, the technique of analyzing legal materials uses qualitative analysis methods. As a result, the authors conclude that, first, the form of legal liability for the Indonesian Limited Liability Company Weda Bay Industrial Park (PT. IWIP) for environmental damage caused by the processing of nickel mines is liability based on acts of violating laws (liability based on fault) and strike liability. Second, conditions for cases of environmental damage resulting from the processing of the Indonesian Limited Liability Company Indonesia Weda Bay Industrial Park (PT. IWIP) nickel mine can be subject to the principle of immediate liability (strict liability), including: every person, group of people, and also includes legal antities such as industrial companies; actions, businesses or activities that use, produce, and utilize B3 (Hazardous and Toxic Materials) and B3 waste; there is a serious threat; and is absolutely responsible for losses without the need to prove and elemen of guilt.